2017
DOI: 10.3390/ma11010026
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Corrosion and In Vitro Bioactivity of Nano-Grained Biomedical Ti-20Nb-13Zr Alloy in a Simulated Body Fluid

Abstract: The bioactivity and the corrosion protection for a novel nano-grained Ti-20Nb-13Zr at % alloy were examined in a simulated body fluid (SBF). The effect of the SPS’s temperature on the corrosion performance was investigated. The phases and microstructural details of the developed alloy were analyzed by XRD (X-ray Diffraction), SEM (Scanning Electron Microscopy), and TEM (Transmission Electron Microscope). The electrochemical study was investigated using linear potentiodynamic polarization and electrochemical im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 52 publications
(60 reference statements)
0
23
0
Order By: Relevance
“…Electrochemical corrosion behaviors of Ti-Nb-Zr-CPP composites primarily depend on the surface passive oxide film, which is determined by their chemical composition. A sequence of possible ion reactions [33][34][35] in simulated physiological solution during the electrochemical process could be expressed as follows:…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical corrosion behaviors of Ti-Nb-Zr-CPP composites primarily depend on the surface passive oxide film, which is determined by their chemical composition. A sequence of possible ion reactions [33][34][35] in simulated physiological solution during the electrochemical process could be expressed as follows:…”
Section: Resultsmentioning
confidence: 99%
“…Ti-64 was the first titanium alloy used for implant materials, and Ti-64 is one of the most used implant materials for dental, orthopaedic and osteosynthesis applications [8]. However, studies have indicated that vanadium, a beta-phase stabilizer, produces oxides harmful to the human body [8,9]. The toxicity of vanadium has encouraged the search for alternative materials to replace Ti-64 [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have indicated that vanadium, a beta-phase stabilizer, produces oxides harmful to the human body [8,9]. The toxicity of vanadium has encouraged the search for alternative materials to replace Ti-64 [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the authors' research group has newly developed a nanograined Ti-20Nb-13Zr at% alloy with a near-b Ti microstructure from the nontoxic elements of Ti, Nb, and Zr, 25 and the electrochemical corrosion and in vitro bioactivity of Ti-Nb-Zr alloys for orthopedic implant applications have been investigated. 26 The developed alloy showed improved hardness and resistance to plastic deformation compared to commercial Ti and G5 alloys.…”
Section: -9mentioning
confidence: 99%